Interleaving cortex-analog mixing improves deep non-negative matrix factorization networks - Nouri, Mahbod; Rotermund, David; Garcia-Ortiz, Alberto; Pawelzik, Klaus R. (Frontiers in Computational Neuroscience, 2025)
Considering biological constraints in artificial neural networks has led to dramatic improvements in performance. Nevertheless, to date, the positivity of long-range signals in the cortex has not been shown to yield improvements. While Non-negative matrix factorization (NMF) captures biological constraints of positive long-range interactions, deep convolutional neural networks with NMF modules do not match the performance of conventional neural networks (CNNs) of a similar size. This work shows that introducing intermediate modules that combine the NMF's positive activities, analogous to the processing in cortical columns, leads to improved performance on benchmark data that exceeds that of vanilla deep convolutional networks. This demonstrates that including positive long-range signaling together with local interactions of both signs in analogy to cortical hyper-columns has the potential to enhance the performance of deep networks.